1987
DOI: 10.1037/0022-3514.53.2.247
|View full text |Cite
|
Sign up to set email alerts
|

Guilt following transgression: An attribution of responsibility approach.

Abstract: People typically experience guilt when they violate sociomoral norms. Using Heider's (1958) attribution of responsibility model in the two experiments reported here, I examined the attributional mediators of posttransgression guilt. The basic design of both studies was a Level of Responsibility X Subject Role factorial. The first study used a role-playing methodology; in the second, subjects generated protocols describing their own past experiences. The second experiment also distinguished between attributions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
116
0
4

Year Published

1988
1988
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(129 citation statements)
references
References 26 publications
7
116
0
4
Order By: Relevance
“…Thus, techniques that minimize attributions of personal accountability are often effective in inducing people to perform behaviors they would otherwise find reprehensible (e.g., Milgram, 1974;Zimbardo, t970); these techniques minimize the guilt associated with such actions. The current findings, combined with those of McGraw (1987), suggest that the conceptual distinction between responsibility and control should be maintained, even though the two are highly correlated. Fear-Perceived Obstacles and Uncertainty?…”
Section: Central Appraisals and Adaptive Functionsmentioning
confidence: 85%
See 1 more Smart Citation
“…Thus, techniques that minimize attributions of personal accountability are often effective in inducing people to perform behaviors they would otherwise find reprehensible (e.g., Milgram, 1974;Zimbardo, t970); these techniques minimize the guilt associated with such actions. The current findings, combined with those of McGraw (1987), suggest that the conceptual distinction between responsibility and control should be maintained, even though the two are highly correlated. Fear-Perceived Obstacles and Uncertainty?…”
Section: Central Appraisals and Adaptive Functionsmentioning
confidence: 85%
“…They suggest that it is not so much whether one can influence what is happening in an unpleasant situation, but whether one feels personally responsible or blameworthy, that is central to the experience of guilt. McGraw (1987) has similarly found attributions of self-blame to be much more closely related to guilt than attributions of selfcausality. Thus, techniques that minimize attributions of personal accountability are often effective in inducing people to perform behaviors they would otherwise find reprehensible (e.g., Milgram, 1974;Zimbardo, t970); these techniques minimize the guilt associated with such actions.…”
Section: Central Appraisals and Adaptive Functionsmentioning
confidence: 97%
“…They hypothesized that behavior that could not be explained by referencing a conscious goal or a normative explanation (Le., behavior in an "explanatory vacuum") would result in negative affect. This reasoning follows from research by McGraw (1987) examining accidental harmdoing (Le., norm violations with no salient explanation), which suggests that negative affect is experienced when norm-violating behaviors lack an accessible justification, Oettingen and colleagues (2006) therefore predicted that normviolating behavior would only result in negative affect when the goal driving that behavior was non conscious, and therefore inaccessible to the actOr. In a collaborative task with a partner, participants either consciously adopted or were nonconsciously primed with the goal to be accommodating (a norm-conforming goal), combative (a norm-violating goal), or were not given a goal (control).…”
Section: The Affective Consequences Of Nonconscious Goal Pursuitmentioning
confidence: 99%
“…Because norm-violations without a salient explanation create negative affect (McGraw, 1987), people in an explanatory vacuum should be highly motivated to interpret and justify their behavior (Stone & Cooper, 2001). Stapel and Koomen have found that when people are extramotivated to explain an ambiguous behavior, they will apply accessible information "more readily and more extensively" (2001, p. 916).…”
Section: Interpreting Bellavior In An Explanatoly Vacllummentioning
confidence: 99%
“…We used a paradigm that extends a method used in previous appraisal research and that primarily relies on laypersons' self-reports (e.g., Ellsworth & Smith, 1988;McGraw, 1987;Roseman, 1984;D. Russell & McAuley, 1986;Stipek, Weiner, & Li, 1989;Weiner, Amirkhan, Folkes, & Verette, 1987).…”
Section: The Nature Of Relation Between Components and Emotionsmentioning
confidence: 99%